Argentina: Peronism and Inclusionary Populist Adaptation to the Pandemic - Lodola, Germán Jorge (2022)
Argentina deviates from the populist script followed by right-wing (exclusionary) leaders under the COVID-19 pandemic; indeed, in many respects, its response has been the polar opposite. The Peronist government of Alberto Fernández reacted swiftly to the health emergency by adopting strict sanitary policies and establishing a science-driven and heroic discourse to represent “the people” in its entirety. Although the lockdown measures had evident demobilizing effects, the government made explicit efforts to mobilize political, scientific, material and human resources to craft a unifying, national response with a broad-based, inclusive coalition. It was a liberal, technocratic and pro-market fraction of the opposition—supported by media conglomerates—that pushed back against Fernández’s aggressive measures, questioning the science and calling for a reopening of the economy. This chapter claims that despite such manifest differences with well-known populist cases, the Argentine government still followed a populist approach to fighting the disease, although of a very different type, rooted in the logic and beliefs of left-wing (inclusionary) populism, which is statist, mobilizational and redistributive.